2004
DOI: 10.1016/j.jpedsurg.2004.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous insulin decreases protein breakdown in infants on extracorporeal membrane oxygenation

Abstract: Background/Purpose-Infants requiring extracorporeal membrane oxygenation (ECMO) have the highest rates of protein catabolism ever reported. Recent investigations have found that such extreme protein breakdown is refractory to conventional nutritional management. In this pilot study, the authors sought to use the anabolic hormone insulin to reduce the profound protein degradation in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 24 publications
(35 reference statements)
0
27
0
Order By: Relevance
“…Associated morbidities include osmotic diuresis, electrolyte imbalance, intraventricular haemorrhage, sepsis, and increased ventilator dependence, retinopathy of prematurity, hospital length of stay and mortality [2][3][4][5][7][8][9]. High rates of proteolysis are also common in low birth weight infants, reducing muscle mass and inhibiting growth [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associated morbidities include osmotic diuresis, electrolyte imbalance, intraventricular haemorrhage, sepsis, and increased ventilator dependence, retinopathy of prematurity, hospital length of stay and mortality [2][3][4][5][7][8][9]. High rates of proteolysis are also common in low birth weight infants, reducing muscle mass and inhibiting growth [10].…”
Section: Introductionmentioning
confidence: 99%
“…All reported insulin infusion trials have used either protocols that fixed insulin dosing to weight or other factors [25], or clinician judgment to determine insulin infusion rates. Positive outcomes of insulin infusion have been reduced proteolysis [10,33,34], improved glucose tolerance, improved caloric intake and weight gain [16,24,[26][27][28][29]31]. Negative reports of hyperinsulinaemia include hypoglycaemia and possible metabolic acidosis due to excessive carbohydrate oxidation [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Farrag, et al identified that the rate of insulin clearance was much higher in neonates compared to a group of healthy adults [46]. In this study, a value of n = 0.9 was used, compared to 0.16 in adults [33], as derived from neonatal insulin infusion studies [18,19,46,53].…”
Section: Parameter Valuesmentioning
confidence: 99%
“…However, endogenous deficiency or lack of effect due to high insulin resistance will have a negative impact on glycemic levels [14]. Additionally, studies have shown reduced proteolysis, and thus preservation of muscle mass associated with insulin therapy [18,19], independent of glucose infusion [20]. However, in the neonate, immature insulin processing can also produce excessive pro-insulin, which is approximately 16x less effective than regular adult insulin, which may also explain why some poor control is exhibited in this population [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation